Nelfinavir inhibits proliferation and induces DNA damage in thyroid cancer cells. Issue 3 (March 2017) - Jensen, Kirk; Bikas, Athanasios; Patel, Aneeta; Kushchayeva, Yevgeniya; Costello, John; McDaniel, Dennis; Burman, Kenneth; Vasko, Vasyl
Abstract : The HIV protease inhibitor Nelfinavir (NFV) inhibits PI3K/AKT and MAPK/ERK signaling pathways, emerging targets in thyroid cancers. We examined the effects of NFV on cancer cells that derived from follicular (FTC), papillary (PTC) and anaplastic (ATC) thyroid cancers. NFV (1–20 µM) was tested in FTC133, BCPAP and SW1736 cell lines. The effects of NFV on cell proliferation were determined in vitro using real-time microscopy and by flow cytometry. DNA damage, apoptotic cell death and expression of molecular markers of epithelial–mesenchymal transition (EMT) were determined by Western blot and real-time PCR. Real-time imaging demonstrated that NFV (10 µM) increased the time required for the cell passage through the phases of cell cycle and induced DNA fragmentation. Growth inhibitory effects of NFV were associated with the accumulation of cells in G0/G1 phase, downregulation of cyclin D1 and cyclin-dependent kinase 4 (CDK4). NFV also induced the expression of γH2AX and p53BP1 indicating DNA damage. Treatment with NFV (20 µM) resulted in caspase-3 cleavage in all examined cells. NFV (20 µM) decreased the levels of total and p-AKT in PTEN-deficient FTC133 cells. NFV had no significant effects on total ERK and p-ERK in BRAF-positive BCPAP and SW1736 cells. NFV had no effects on the expression of EMT markers (Twist, Vimentin, E- and N-Cadherin), but inhibited the migration and decreased the abilities of thyroid cancer cells to survive in non-adherent conditions. We conclude that NFV inhibits proliferation and induces DNA damage in thyroid cancer cell lines. Our in vitro data suggest that NFV has a potential to become a new thyroid cancer therapeutic agent.